8a - 3b + 7 - (2a + b - 4) = 6a = -11 + 4b
Simplifying: 8a + -3b + 7 + -1(2a + b + -4) = 0
Reorder the terms: 8a + -3b + 7 + -1(-4 + 2a + b) = 0
8a + -3b + 7 + (-4 x -1 + 2a x -1 + b x -1) = 0
8a + -3b + 7 + (4 + -2a + -1b) = 0
Reorder the terms: 7 + 4 + 8a + -2a + -3b + -1b = 0
Combine like terms: 7 + 4 = 11
11 + 8a + -2a + -3b + -1b = 0
Combine like terms: 8a + -2a = 6a
11 + 6a + -3b + -1b = 0
Combine like terms: -3b + -1b = -4b
11 + 6a + -4b = 0
Solving 11 + 6a + -4b = 0
Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-11' to each side of the equation.
11 + 6a + -11 + -4b = 0 + -11
Reorder the terms: 11 + -11 + 6a + -4b = 0 + -11
Combine like terms: 11 + -11 = 0
0 + 6a + -4b = 0 + -11
6a + -4b = 0 + -11
Combine like terms: 0 + -11 = -11
6a + -4b = -11
Add '4b' to each side of the equation. 6a + -4b + 4b = -11 + 4b
Combine like terms: -4b + 4b = 0
6a + 0 = -11 + 4b
6a = -11 + 4b
6a = -11 + 4b is your answer
Hope I helped ; )